The Dialectics of Equality and Social Differentiation in Tafsir Al-Azhar - Balya Haikal Hizbullah Al Kautsar; M. Sihabudin; Muhammad Athif Awadh; Ahmad Nabil Annuha (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
Despite the growing scholarship on Hamka’s Tafsir Al-Azhar, studies examining the dialectical relationship between musawah (equality) and al-tafadhul (social differentiation) remain limited. Existing research generally discusses Hamka’s social thought in partial ways without systematically analyzing how equality and hierarchy are simultaneously constructed within his Qur’anic interpretation. This study aims to analyze the construction of musawah and al-tafadhul in Tafsir Al-Azhar through Teun A. Van Dijk’s Critical Discourse Analysis (CDA). Using a qualitative approach, the study examines selected verses related to social relations, leadership, human equality, and moral distinction. The analysis applies Van Dijk’s three dimensions of CDA: textual structure, social cognition, and social context. The findings reveal that Hamka promotes human equality by rejecting superiority based on race, lineage, and social class, while simultaneously maintaining moral differentiation based on faith, knowledge, righteous deeds, and ethical responsibility. This discourse reflects Hamka’s Islamic reformist orientation, socio-political experiences, and Minangkabau egalitarian culture. The study argues that Tafsir Al-Azhar functions not only as normative exegesis but also as a medium of social construction negotiating Islamic egalitarianism and moral hierarchy within Muslim society.